2014
DOI: 10.1186/1297-9716-45-27
|View full text |Cite
|
Sign up to set email alerts
|

Passive immunization to reduce Campylobacter jejuni colonization and transmission in broiler chickens

Abstract: Campylobacter jejuni is the most common cause of bacterium-mediated diarrheal disease in humans worldwide. Poultry products are considered the most important source of C. jejuni infections in humans but to date no effective strategy exists to eradicate this zoonotic pathogen from poultry production. Here, the potential use of passive immunization to reduce Campylobacter colonization in broiler chicks was examined. For this purpose, laying hens were immunized with either a whole-cell lysate or the hydrophobic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
3
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 28 publications
4
72
3
2
Order By: Relevance
“…In the present study, no protection against C. jejuni colonization was detected in chickens fed HEYP compared to control animals. This is in contrast to the results of Hermans et al, (2014) and Vandeputte et al, (2019a), the latter applying the same vaccines and procedures as used in this study, but using fresh yolks. A possible explanation is that lyophilization resulted in a 16-fold decline of the Campylobacter-specific antibody titer in the yolk, as determined by ELISA.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…In the present study, no protection against C. jejuni colonization was detected in chickens fed HEYP compared to control animals. This is in contrast to the results of Hermans et al, (2014) and Vandeputte et al, (2019a), the latter applying the same vaccines and procedures as used in this study, but using fresh yolks. A possible explanation is that lyophilization resulted in a 16-fold decline of the Campylobacter-specific antibody titer in the yolk, as determined by ELISA.…”
Section: Discussioncontrasting
confidence: 69%
“…Campylobacter-specific IgY titers in egg yolks were determined before and after lyophilization, as previously described by Hermans et al, (2014) with minor changes to the protocol. Egg yolks were diluted 1/5 (vol/vol) in HBSS, mixed thoroughly, and incubated overnight at 4 C. Lyophilized egg yolks were first diluted 1/2 (wt/ vol) in HBSS because half of the egg yolk consists of water (Bizanov, 2017).…”
Section: Determination Of Egg Yolk Igy Titersmentioning
confidence: 99%
“…Campylobacter jejuni is often considered a harmless commensal inhabitant of the chicken gut, and the immune response to it in the intestinal tract is thought to be tolerogenic (Hermans et al, 2014). In our previous study the counts of Campylobacter-like spp.…”
Section: Discussionmentioning
confidence: 94%
“…A small trial using the ionophore coccidiostat salinomycin in feed found that it offered no protection to persistent colonization of 14‐day‐old birds by C. jejuni following a high dose (10 9 cfu) oral inoculum (Johansen, Bjerrum, Lund, & Pedersen, ). By contrast, a small‐scale trial incorporating yolk (5% w/w) from eggs of hens immunized with adjuvanted C. jejuni lysate into chick feed (Hermans et al., ) demonstrated substantial protection against colonization following oral challenge with 10 4 cfu of the same strain of C. jejuni at 10 days of age. A reduction in cecal counts of more than five log 10 units was observed in test animals at 13 days of age, and transmission to in‐contact birds was prevented.…”
Section: Interventions Complementary To Biosecurity and Hygienementioning
confidence: 98%